History of the Interchurch World Movement of North America - Fosdick, Raymond B. (Raymond Blaine), 1883-1972.
Two volume typescript entitled "History of the Interchurch World Movement of North America" containing official documents of the movement which was founded in 1918 as an interfaith Christian organization to coordinate Protestant church resources in evangelizing non-Christians throughout the world by focusing on Christian education, medical and sanitary work, and social service. Documents the establishment of the organization, distribution and publication of surveys, educational activities, field activities, financial activities, and the liquidation of the organization's assets.
Lawyer and member of the Business Men's Committee, Interchurch World Movement of North America.
Collection material in English.
Keywords: Interchurch World Movement of North America; Evangelistic work; Protestant churches; Lawyers